Framework for improving clash management process for the construction management team using industrialized building product - Jarullah, Mustafa Fawwaz (2020)
The construction industry continually facing problems in its projects. The clashes that occur during construction phase consider one of the major problems faced by the construction project. Furthermore, controlling the construction clashes consider a crucial need to decrease the waste of time and cost in the construction project. The costs of rework in poorly managed projects can be as much as 25%-30% of contract value and 10% of the total project costs. Despite all the efforts to avoid the construction clashes during design stage, there are no ideal construction process with zero clashes, and it is almost becoming a rare thing for a project not to have clashes. Hence, clash management become a normal occurrence in all construction projects. The management of the project consider one of the main reasons to cause clashes in design and construction. As the construction industry seeks for improvement overtime, new tools and innovation has been interduce to the industry to improve the conventional practice such as industrialized building system (IBS) and building information modeling (BIM). CITP 2016-2020 highlights the intention of Malaysian government to introduce these industrialized building products to the construction industry and increase the level of adoption. The reason to implement these new products is to enhance interactions between different team members and to reduce the clashes that occur from their lacking. Therefore, there is a need to improve the clash management process during on-going construction stage in order to support the use of industrialized building product in the AEC industry in Malaysia. The purpose of this study is to discuss how can the project management team improves the clash management process during on-going construction stage. This study uses literature review to identify the key areas that the industrialized building product can support the project team during clash management and to understand the project team factors contributing towards clashes that occur during on-going construction. This study recommends aligning the industrialized building products to the management team actions during the clash management process which can improve construction productivity, and thereby, reducing future reworks. Results of this study would provide a framework for the management team actions through the clash management process and recommends the required areas for improvements. This study contributes in documenting the clash management process and the current practice, and improves the clash management process for the project management team during the construction stage. Also, this study contributes in supporting the implementation of the industrialized building product towards automating the clash management process in the future. Results of this study will lead towards supporting CITP 2016-2020 plan to increase the adoption of the BIM and IBS in the construction industry in Malaysia.